FAMILY COMPETITIVE ECONOMIC PERFORMANCE WITH FINANCIAL LITERACY: COMMUNITY SERVICE IN PONDOK AREN - Wahyono, Tri; Perkasa, Didin Hikmah; Karyatun, Subur; Supryadi, Didy Ika; Kuswibowo, Christian; Putra Saratian, Eko Tama; Soelton, Mochamad (Lembaga Penelitian Dan Pengabdian Pada Masyarakat (LPPM) Institut Bisnis dan Informatika (IBI) Kosgoro 1957, 2024)
PKM Partners is Pondok Aren District in the Department of Cooperatives & UMKM located on Jl. Graha Raya Bintaro No.1, Parigi Baru, Tangerang, South Tangerang City, Banten 15228. Pondok Aren District is growing quite rapidly, with a population of around 294,996. This is directly proportional to the number of MSMEs reported based on the SKDU document of around 1,373. Currently, the government, through the Financial Services Authority (OJK), is calling on the public to continue to encourage the progress of the Sharia Financial Industry which has grown rapidly in the last five years both in terms of the number of players and sharia financial assets in banking, capital markets and IKNB [1]. In Indonesia, family entrepreneurship has begun to emerge and this can be seen from various franchise businesses such as fast food franchises, retail store franchises to service businesses and so on. With the problems above, the community service team held business plan outreach activities in creating family entrepreneurship. The development of family entrepreneurship can also support economic growth in countries such as the United States where 90 percent of the 15 million companies are family companies and have contributed 40% of the GNP of the United States, while with an understanding of Business Planning in developing family entrepreneurship, it can prevent disagreements and conflict occurs in the company, so that in the end it can reduce poverty levels and improve community welfare. Family economic problems can be overcome by carrying out various family-based entrepreneurial activities. Family-based entrepreneurship can be developed to reduce dependence on work from companies both government and private.